2002
DOI: 10.1093/jn/132.1.72
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid Is Superior to Eicosapentaenoic Acid as the Essential Fatty Acid for Growth of Grouper, Epinephelus malabaricus

Abstract: Juvenile grouper (Epinephelus malabaricus) were fed seven experimental diets, one control diet and one reference diet for 12 wk to determine the dietary requirement of grouper for docosahexaenoic (DHA) and eicosapentaenoic (EPA) acids. Each of the seven diets contained 1 g/100 g DHA and EPA in various combinations and 9 g/100 g tristearin. The control diet contained 1 g/100 g trilinolenin and trilinolein (3:1, wt/wt), and no supplemental EPA or DHA. The reference diet contained only natural oils from a mixture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
65
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 38 publications
8
65
0
1
Order By: Relevance
“…The n 6 FAs are commonly present in vegetable oils and eggs (especially C 20:4 n 6 in lecithine) and n 3 FAs are commonly present in fish oil (Flayeh, 2000;Wu et al, 2002). A noticeable quantity of n 6 FAs was detected in Iraqi mothers' breast-milk, but it was still lower than that of most milk samples from other countries (Innis, 1991;Jorgensen et al, 1995;Jensen, 1999;Wu et al, 2002). Iraqi breast-milk was particularly poor in n 3 FAs.…”
Section: Discussionmentioning
confidence: 99%
“…The n 6 FAs are commonly present in vegetable oils and eggs (especially C 20:4 n 6 in lecithine) and n 3 FAs are commonly present in fish oil (Flayeh, 2000;Wu et al, 2002). A noticeable quantity of n 6 FAs was detected in Iraqi mothers' breast-milk, but it was still lower than that of most milk samples from other countries (Innis, 1991;Jorgensen et al, 1995;Jensen, 1999;Wu et al, 2002). Iraqi breast-milk was particularly poor in n 3 FAs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the percentage of DHA and the ratio of n3/n6 in PT colostrum are lower than in FT colostrum. This indicates that there is a decrease in the absolute and relative amounts of DHA, the most important FA for infant growth (Wu et al, 2002). Generally, it has been observed that the level of n3/n6 for both groups (mainly PT-group) is lower than that recommended by WHO for infant optimum nutrition (0.1).…”
Section: Relation Of Colostrum Fatty Acids To Mother-serum Fatty Acidsmentioning
confidence: 91%
“…The basal diet was composed of solvent-extracted fishmeal 651·5 g kg 1 , solvent-extracted corn starch 43·5 g kg 1 , solvent-extracted -starch 43·5 g kg 1 , vitamin mixture 40 g kg 1 , mineral mixture 80 g kg 1 , -cellulose 11·5 g kg 1 and carboxymethyl-cellulose (binder) 30 g kg 1 [30]. Proximate analysis of the basal diet showed a crude protein concentration of 52·3%, moisture content of 3·5%, ash content of 9·8% and a residual amount of lipid (0·9%).…”
Section: Experimental Dietmentioning
confidence: 99%